Representable functors, Yoneda Lemma, and universal objects - Javier Díaz, Isaac; Pompeyo Guitérrez, Carlos Ariel (JOURNAL OF BASIC SCIENCES, 2025)
In this work we explore the concepts of representability and universal object, as well as Yoneda’s Lemma, which belong to Category Theory. We provide several examples to illustrate the concepts. In order to do this, we consider objects coming from different mathematical fields, such as Linear Algebra, Topology, Ring Theory, among others. Besides, we provide proofs for the results.
Keywords: Representable functors; Yoneda’s lemma; Category Theory; Natural Transformations